Entrepreneurship: Productive, unproductive, and destructive - Baumol, William J. (Journal of Business Venturing, 1996)
The basic hypothesis is that, while the total supply of entrepreneurs varies among societies, the productive contribution of the society's entrepreneurial activities varies much more because of their allocation between productive activities such as innovation and largely unproductive activities such as rent seeking or organized crime. This allocation is heavily influenced by the relative payoffs society offers to such activities. This implies that policy can influence the allocation of entrepreneurship more effectively than it can influence its supply. Historical evidence from ancient Rome, early China, and the Middle Ages and Renaissance in Europe is used to investigate the hypotheses.